Professores (as) negros (as) e relações raciais: percursos de formação e transformação - Patricia Maria de Souza Santana (2003)
This text has as main objective to possibility a comprehension about different visions and postures of black teachers on the race relations question. Starting from oral statement of five black teachers (four women and one man) of public school in Belo Horizonte the author tries to describe personal and professional experiences of those teachers with racial discrimination throughout their biographic trajectories and analyzes how those experiences affected the way of those teachers face the race relations question in their personal and professional trajectories. This work was developed taking as presuppose the importance of biographic trajectories in the process of teachers identity building. The author believes that some contexts lived by those teachers can produce different ways of be in the word and it can possibility a better comprehension that there are different forms of understanding and signifying racial discriminations experienced by them. This diversity of posture is closely tied to the way of race relations are configured in Brazil. The myth of racial democracy that is largely diffused in Brazilian society produces a very peculiar form of race relations manifestation that is marked by silenciamentos and ambiguities. For interviewed teachers it was difficult to understand the reason of suffered racial discriminations and to react face them. Each teacher had a specific reaction in different moments of his or her lives: they can have a posture of negation of the prejudice against them, conformation or no perception of the prejudice. Changes in the perception of how racism has been manifested in the society and in the live of each teacher life will depend on a long personal reelaboration process that is marked by doubts, silences, embarrassments, anguishes, resentments and revolt. The individual biography becomes linked to the social and historical moment that each one was and has been inserted. The development of experiences lived by those teachers in their pedagogical practice express the diversity present in their trajectories. But intra and extra scholar contexts are fundamental to emerge political and pedagogical practices turned to racial question. It is necessary to formulate and introduce more effective public politics in order to promote the racial equality in general society and in the educational system in special.